2005
DOI: 10.1111/j.1740-8261.2005.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Distal Phalanx and Navicular Bone in an Andalusian Stallion

Abstract: We describe the clinical findings and radiographic abnormalities of a horse with a bipartite distal phalanx and a bipartite navicular bone of the right forelimb. Associated findings including suspected keratoma and degenerative joint disease of the distal interphalangeal joint are described and possible etiologies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Navicular bone partition is a rare, likely congenital, condition that has been described in horses . Multiple variations of the condition have been reported, including bi‐ and tripartition of the bone, unilateral and bilateral disease, as well as a case in which the distal phalanx was also divided .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Navicular bone partition is a rare, likely congenital, condition that has been described in horses . Multiple variations of the condition have been reported, including bi‐ and tripartition of the bone, unilateral and bilateral disease, as well as a case in which the distal phalanx was also divided .…”
mentioning
confidence: 99%
“…This may be the result of a disturbance to the bone’s blood supply (such as vascular microtrauma or intra‐articular blood vessel compression) at the stage of gestation when angiogenesis occurs in the precursor cartilage model, thus leading to defective endochondral ossification and ultimately partitioning of the bone . Other authors have suggested the syndrome may be a form of mild polydactyly, as evidenced by a case of a bipartite distal phalanx and navicular bone in an Andalusian stallion . It is therefore possible that not all congenital partitioned navicular bones arise by the same pathophysiological process.…”
mentioning
confidence: 99%
See 3 more Smart Citations